2020
DOI: 10.1002/cpe.6077
|View full text |Cite
|
Sign up to set email alerts
|

An improved agglomerative hierarchical clustering anomaly detection method for scientific data

Abstract: Anomaly detection tries to find out the data that disobeys the rule of majority data or expected patterns. The traditional hierarchical clustering algorithms have been adopted to detect anomaly, but have the disadvantages of low effectiveness and unstability. So we propose an improved agglomerative hierarchical clustering method for anomaly detection. It dynamically adjusts the optimum clustering number according to the self-defined criterion to save the trouble of manually picking clustering number, and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Clustering techniques used for anomaly detection include fuzzy c-means clustering (FCM) [17], K-means clustering [18], and hierarchical clustering [10]. Shi et al [19] demonstrated that hierarchical clustering was superior by comparing hierarchical clustering with k-means clustering and FCM, which are the most popular clustering techniques in anomaly detection, using the scientific data HTRU2 dataset [20] and tensile test dataset. Shi et al [19] purposed improved agglomerative hierarchical clustering (IAHC), which dynamically adjusts the clustering linkage modes and the number of clusters during the hierarchical clustering algorithm iterations.…”
Section: Clustering-based Anomaly Detectionmentioning
confidence: 99%
“…Clustering techniques used for anomaly detection include fuzzy c-means clustering (FCM) [17], K-means clustering [18], and hierarchical clustering [10]. Shi et al [19] demonstrated that hierarchical clustering was superior by comparing hierarchical clustering with k-means clustering and FCM, which are the most popular clustering techniques in anomaly detection, using the scientific data HTRU2 dataset [20] and tensile test dataset. Shi et al [19] purposed improved agglomerative hierarchical clustering (IAHC), which dynamically adjusts the clustering linkage modes and the number of clusters during the hierarchical clustering algorithm iterations.…”
Section: Clustering-based Anomaly Detectionmentioning
confidence: 99%
“…e improved condensed hierarchical clustering algorithm proposed in this paper is utilized to cluster text information, and the central point of each cluster is figured out. e calculation formula is shown in formula (22) [23][24][25][26][27]:…”
Section: Name Disambiguation and Alumni Identificationmentioning
confidence: 99%
“…With this principle, a kinematic-based data anomaly detection method is proposed in our work. Forming part of the widely used unsupervised anomaly detection techniques, clusteringbased methods can identify anomalies without prior knowledge and are suitable for multiple data types [28]. One of the most popular clustering methods, K-means clustering, has been applied to detect abnormal data [29].…”
Section: Anomaly Detectionmentioning
confidence: 99%